The effect of administering mangosteen rind extract (garnicia mangostana l) compared with glimepiride to the blood sugar levels of white male rat (rattus norwegicus l) induced by streptozotocin - As'ari, Hasyim; Mahartini, Dewi Mutmainnah (Folia Medica Indonesiana, 2017)
The purpose of this study is to prove the differential effect of administering the mangosteen Rind extract due to lowering the blood sugar levels of Winstar white male rats induced by streptozotosin (STZ). This study used a randomized design of the ramdomized posttest only control group design. The sample consisted of 4 groups with a sample size of 7 animals each group of rats. All samples were prepared STZ induction of diabetes with a single dose of 50 mg/Kg BW through intraperitoneal (IP). K0 (control group; given 1% CMC 1 cc/day), K1 (treatment group 1; given 0,054 mg glimepiride/200 grBW, K2 (treatment group 2; given mangosteen Rind extract 50 mg/Kg BW), K3 (treatment group 3; given the mangosteen Rind extract 100 mg/Kg BW). Timing of therapy in each group was for 7 days. Shapiro-Wilk normality test (a=0.05) in the BW D variable data, pre-post STZ GDP and D GDP. Testing homogeneity used Levene's test. When data distribution was normal and homogenous, it used an ANOVA deferential test. When data distribution was normal and inhomogeneous, it proceed to apply T-test with 2 free samples. The results: 1) There were significant differences between K0 D GDP with K1 (p=0.015), K0 to K2 (p=0.003) and group K0 to K3 (p=0.002), 2) Whereas no difference was shown in the K1 with K2 (p=0.442), K1 to K3 (p=0,401) and K2 to K3 (p=0.878). Conclusion: The administration of mangosteen Rind extract doses of 50 and 100 mg/kg bw/day did not differ in lowering blood sugar levels compared with glimepiride administration of a dose of 0.054 mg/200 grBW rat/day. Mangosteen Rind extract dose of 100 mg/kg bw/day and 50 mg/kg bw/day did not provide a significant difference in lowering blood sugar levels.